A classification of lipoprotein disorders: implications for clinical management. (June 2011) - Sullivan, David R; Lewis, Barry
Several plasma lipoprotein disorders are classic modifiable risk factors for atherosclerotic cardiovascular disease, and they arise from various causes. Other forms of lipoprotein disorder are associated with pathological consequences such as acute pancreatitis. Like many other risk factors, most lipoprotein disorders are the result of gene––environment interactions. Furthermore, lipoprotein disorders may be secondary to other disease states. The pattern of lipid disturbance and its clinical consequences are best understood in terms of disruption to the normal metabolism of lipoproteins, levels of which may increase or decrease accordingly. This article reviews the framework of the classification of lipoprotein disorders in order to consolidate a clinical approach that is based on the etiology and pathophysiology of the underlying metabolic disturbance.